Effects of dietary supplementation of Enterococcus faecium postbiotics on growth performance and intestinal health of growing male mink - Cao, Lin; Sun, Fengxue; Ren, Qifeng; Jiang, Ziyi; Chen, Jian; Li, Yalin; Wang, Lihua (Frontiers in Veterinary Science, 2024)
Recent studies have demonstrated that postbiotics possess bioactivities comparable to those of probiotics. Therefore, our experiment aimed to evaluate the effects of postbiotics derived from Enterococcus faecium on the growth performance and intestinal health of growing male minks. A total of 120 growing male minks were randomly assigned to four groups, each with 15 replicates of two minks. The minks in the four groups were fed a basal diet supplemented with 0 (control), 0.05%, 0.1% and 0.15% postbiotics derived from Enterococcus faecium (PEF), respectively. Compared with the control, PEF improved feed/gain (F/G) during the first 4 weeks and the entire 8 weeks of the study (P<0.05), in addition, 0.1% PEF improved average daily gain (ADG) during the first 4 weeks and the entire 8 weeks of the study (P<0.05), while 0.15% PEF improved ADG during the first 4 weeks of the study (P<0.05). Consequently, 0.1% PEF minks displayed greater body weight (BW) at week 4 and week 8 (P<0.05), and 0.15% PEF minks had greater BW at week 4 (P<0.05) compared to minks in the control. Furthermore, compared with the control, both 0.05% and 0.1% PEF enhanced apparent digestibility of CP and EE (P<0.05) in the initial 4 weeks, while both 0.1% and 0.15% PEF enhanced apparent digestibility of CP and DM in the final 4 weeks (P<0.05). Additionally, trypsin activity was elevated in the 0.1% and 0.15% PEF groups compared to the control (P<0.05). In terms of intestinal morphology, PEF increased villus height and villus/crypt (V/C) in jejunum (P<0.05), and both 0.1% and 0.15% PEF decreased crypt depth, while increased villus height and V/C in duodenum (P<0.05) compared to the control. Supplementation with 0.1% PEF increased the SIgA levels, while decreased IL-2, IL-8 and TNF-α levels in the jejunum (P<0.05). Compared with the control, Enterococcus faecium postbiotics decreased the relative abundances of Serratia and Fusobaterium (P<0.05). In conclusion, the results indicate that the growth performance, digestibility, immunity, and intestine development of minks are considerably affected by Enterococcus faecium postbiotics. Particularly, dietary supplementation with 0.1% Enterococcus faecium postbiotics provides greater benefits compared to supplementation with 0.05% and 0.15%.